2014
DOI: 10.1002/tox.21983
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of silk gland damage caused by phoxim exposure and protection of phoxim‐induced damage by cerium chloride in Bombyx mori

Abstract: It is known that exposure to organophosphorus pesticides (OP) including phoxim can produce oxidative stress, neurotoxicity, and greatly attenuate cocooning rate in the silkworm, Bombyx mori. Cerium treatment has been demonstrated to relieve phoxim-induced toxicity in B. mori; however, very little is known about the molecular mechanisms of silk gland injury due to OP exposure and protection of gland damage due to cerium pretreatment. The aim of this study was to evaluate silk gland damage and its molecular mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Here, we address a number of issues in the report by Hong et al in Environmental Toxicology . In addition to our concerns on this report, 11 other papers by Hong and coworkers in Environmental Toxicology should be interpreted with outmost scepticism . Preferably, the papers should be re‐assessed in light of recent concerns that have been raised about the reports from Hong and coworkers.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Here, we address a number of issues in the report by Hong et al in Environmental Toxicology . In addition to our concerns on this report, 11 other papers by Hong and coworkers in Environmental Toxicology should be interpreted with outmost scepticism . Preferably, the papers should be re‐assessed in light of recent concerns that have been raised about the reports from Hong and coworkers.…”
mentioning
confidence: 95%
“…Moreover, the committee found that some of the original data were missing . It should be noted that none of results in the 11 publications in Environmental Toxicology have been corrected, although they presumably have the same statistical error. Curiously, Hong and coworkers have published a correction to a figure on histopathology to one paper in Environmental Toxicology , but the authors neglected to correct the erroneous statistical analysis of 184 separate results that have ratio of 5% between the SE and mean in the same article …”
mentioning
confidence: 99%
“…Phoxim (organophosphate) and fenpropathrin (pyrethroid) are high effect, low poison, low leftover and broad-spectrum, and often used for agricultural pest management (Isaacs et al, 2005). Previous studies suggested that phoxim can induce oxidative stress and damages of silkworm larval midgut and silk gland after short-term exposure (Su et al, 2014;Li et al, 2014). Furthermore, malondialdehyde (MDA) content and GST activity were increased in the midgut and fat body of the silkworm larvae after short-term exposure to phoxim (Yu et al, 2011).…”
Section: Introductionmentioning
confidence: 97%
“…In recent years, large-scale abuse of phoxim pesticide has significantly affected mulberry, leading to pesticide poisoning of silkworm, and significantly restricting the development of sericulture 10 11 . For example, synthetic phoxim has been shown to impede fibroin synthesis, resulting in a decline of silk production of silkworm 12 13 . TiO 2 NPs, as a new additive, can not only improve silk production of silkworm 14 15 , but also alleviate phoxim-caused metabolic disorders of silk gland 13 16 .…”
mentioning
confidence: 99%